Strategi Kesantunan Berbahasa pada Media Sosial WhatsApp Berdasarkan Level Pendidikan - Riska Amalia Hafid; Serliana Serliana; Gusnawaty Gusnawaty; Ikhwan M. Said (Al-Lisan: Jurnal Bahasa, 2022)
Language politeness in social media is still often ignored. The article aims to describe teenagers' politeness strategies in social media conversations, especially in the WhatsApp group of junior high schools, senior high schools, and colleges. The research was quantitative and qualitative descriptive, and the population was complete sentences in WhatsApp group conversations. The period of recording the conversation with each group is during September 2021. The data collection technique is by exporting the conversation data to Ms. Words. The data were arranged based on the entry date, then coded using Brown & Levinson's politeness theory. The interpretation of the data classification results used the approach of Makassar's cultural perspective. The findings showed that in social media WhatsApp, the teenagers talked more frequently used three kinds of politeness strategies. 1) Bald on record involving questions, commands, and requests. Teenagers use this strategy from three-level of education. 2) Positive strategies involve jokes, identity, and paying attention. The college and high schools teenagers use jokes and identity. However, paying attention's strategy is just used by college teenagers. 3) Negative strategies include apologies, be-thankful, and questions. College and high schools teenagers use the apology and thank strategies. Nevertheless, teenagers from the high school level only used negative politeness in asking questions. In conclusion, the level of education of teenagers determines the use of politeness strategy in social media. The implication is that teachers and stakeholders pay more attention to students' language politeness building, especially in speaking politely to others, so their interaction is harmonious with their communities.